STRATEGI PENDIDIKAN UNTUK MELESTARIKAN ARSITEKTUR TRADISIONAL DALAM RANGKA MEMPERKUAT JATI DIRl BANGSA - Sumarjo H Sumarjo H (LPMPP Universitas Negeri Yogyakarta, 2001)
Whether is it reconized or not, architecture works reflex cultural characteristic of people whohave built them. Phenomena existing at the city and a part the village, many buildings of traditionalhouse were demolished to substitute them for the new building of 'modern' style. Undirectedapplication of foreign culture elements can cause elimination of nation cultural values which willeventually weaken the personality and spirit of nationalism.Indonesian b-aditional architecture that has long time established evolutively is a shiningexample enriched with nation culture values. Physical f m , lay out, structure, and vatiations intraditional a r c h i t e m reflex the values of religion, social, economy, solidarity, technology and art.Superiority in Indonesian traditional architecture lies on the strength the values of religion, socialand art. The all three values constitute the identity of nation culture The educational strategy oftraditional architecture through formal and nonformal educations. rn formal education include in thesubject matter curriculum. in nonfonnal educations thmugh semi tan tradition norm revitalism andpermission to built